Arbuscular mycorrhiza Symbiosis Induces a Major Transcriptional Reprogramming of the Potato SWEET Sugar Transporter Family - Manck-Götzenberger, Jasmin; Requena, Natalia (Frontiers in Plant Science, 2016)
Biotrophic microbes feeding on plants must obtain carbon from their hosts without killing the cells. The symbiotic arbuscular mycorrhizal (AM) fungi colonizing plant roots do so by inducing major transcriptional changes in the host that ultimately also reprogram the whole carbon partitioning of the plant. AM fungi obtain carbohydrates from the root cortex apoplast, in particular from the periarbuscular space that surrounds arbuscules. However, the mechanisms by which cortical cells export sugars into the apoplast for fungal nutrition are unknown. Recently a novel type of sugar transporter, the SWEET, able to perform not only uptake but also efflux from cells was identified. Plant SWEETs have been shown to be involved in the feeding of pathogenic microbes and are, therefore, good candidates to play a similar role in symbiotic associations. Here we have carried out the first phylogenetic and expression analyses of the potato SWEET family and investigated its role during mycorrhiza symbiosis. The potato genome contains 35 SWEETs that cluster into the same four clades defined in Arabidopsis. Colonization of potato roots by the AM fungus Rhizophagus irregularis imposes major transcriptional rewiring of the SWEET family involving, only in roots, changes in 22 of the 35 members. None of the SWEETs showed mycorrhiza-exclusive induction and most of the twelve induced genes belong to the putative hexose transporters of clade I and II, while only two are putative sucrose transporters from clade III. In contrast, most of the repressed transcripts (10) corresponded to clade III SWEETs. Promoter-reporter assays for three of the induced genes, each from one cluster, showed re-localization of expression to arbuscule-containing cells, supporting a role for SWEETs in the supply of sugars at biotrophic interfaces. The complex transcriptional regulation of SWEETs in roots in response to AM fungal colonization supports a model in which symplastic sucrose in cortical cells could be cleaved in the cytoplasm by sucrose synthases or cytoplasmic invertases and effluxed as glucose, but also directly exported as sucrose and then converted into glucose and fructose by cell wall-bound invertases. Precise biochemical, physiological and molecular analyses are now required to profile the role of each potato